Sifat Optik Lapisan Tipis ZnO - Aris Doyan; Humaini Humaini (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
The aim of this research is to manufacture and characterize optical properties of ZnO thin layer which is deposited on glass substrate by sol-gel spin-coating method, through the process of growing ZnO thin layer of zinc acetate dehydrate (ZnAc) precursor on glass substrate with spin speed 2000 rpm for 30 minutes on a spin coater plate. The growth of layers by the sol-gel method of spin-coating is determined by the length of time of spin rotation which is related to the thickness of the thin layer. The Samples on the substrate in anneling at 400 oC and 500 oC for 1.5 hours to obtain a thin layer of ZnO. The obtained layer was characterized by UV-Vis test to determine the optical properties of the coating which include absorbance, transmittance, and bandgap energy. UV-Vis testing states that, the higher concentration of ZnO solution then the layer looks increasingly not transparent so that the transmittance value is smaller, otherwise the absorbance value of the layer becomes higher. This is indicated by the results obtained, at 1 M molarity concentration obtained the value of transmittance (50. 40%), while at a concentration of 0.7 M obtained greater transmittance value (75.24%) at the same heating temperature 500 oC. The gap energy is a forbidden area where electrons are located between the valence bands filled by the electrons and the empty conduction bands of the electrons. With respect to the photon energy to excite the electrons, the annealing treatment will affect the magnitude of the gap energy. High annearance temperature obtained a smaller gap energy compared with lower anneling temperatures. The obtained energy gap of 2.1 eV at 400 ÃÂ°C annealing temperature is greater than 0.1 eV compared to the heating temperature of 500 oC at 2.0 eV.